2023
DOI: 10.21203/rs.3.rs-3182841/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Andes virus mRNA vaccines: comparison of unmodified and modified mRNA platforms

Abstract: Andes virus (ANDV) is a rodent-borne zoonotic orthohantavirus endemic in South America that causes hantavirus pulmonary syndrome in humans, with up to a 40% case fatality rate. We developed ANDV mRNA vaccines based on the M segment of the viral genome that codes for glycoproteins Gn and Gc in a single open reading frame of glycoprotein precursor (GPC). We generated RNAs either with regular uridine (U-mRNA) or N1-methylpseudouridine (m1Ψ-mRNA). Mice immunized by either ANDV U-mRNA or m1Ψ-mRNA developed similar … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…We used a modified nucleotide (5-methoxyuridine) with the expectation of reduced innate immune responses to improve the expressions of antigens. Bukreyev et al recently reported that mRNA-LNP vaccines against Andes virus with and without modified nucleotides exhibited no significant differences in protection and immunogenicity in a hamster model ( 65 ). Intriguingly, they dephosphorylated IVT-mRNA and removed dsRNA by a method using cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…We used a modified nucleotide (5-methoxyuridine) with the expectation of reduced innate immune responses to improve the expressions of antigens. Bukreyev et al recently reported that mRNA-LNP vaccines against Andes virus with and without modified nucleotides exhibited no significant differences in protection and immunogenicity in a hamster model ( 65 ). Intriguingly, they dephosphorylated IVT-mRNA and removed dsRNA by a method using cellulose.…”
Section: Discussionmentioning
confidence: 99%